Pengaruh Upah dan Insentif Terhadap Kinerja Karyawan pada Kantor PT. PP London Sumatera Indonesia TBK - Suriono, Hadi; Malawat, Muh. Saleh; Fhitri, Nisfu; Normansyah, Normansyah; Wahyuni, Dian; Rumondang, Rumondang; Pratiwi, Widya Ayu (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The background underlying this research is the performance of employees at the PT Office. PP London Sumatra Indonesia Tbk which must always be maintained in order to always be in the best position, that variable wages and incentives are accompanying factors in improving employee performance. The theory used in this writing is human resource management theory with a greater focus on wage and incentive factors and employee performance which are the variables in this research. The method used in this research is a survey approach, the type of research is quantitative descriptive and the nature of the research is explanatory. Data collection methods are questionnaires, interviews and documentation studies. The population is all employees at the PT Office. PP London Sumatra Indonesia Tbk had 586 employees in 2013 and the sample size of the entire population was determined to be 85 employees. The research results show that simultaneously there is a very significant influence between wages and incentives on employee performance at the PT Office. PP London Sumatra Indonesia Tbk and partially shows that there is a significant influence between wages and incentives on employee performance at the PT Office. PP London Sumatra Indonesia Tbk and partially the most dominant influence on employee performance is wages. The conclusion of the research results, simultaneously and partially, wages and incentives have a significant effect on employee performance at the PT Office. PP London Sumatra Indonesia Tbk. To further improve employee performance, the leadership of the PT. PP London Sumatra Indonesia Tbk needs to further increase wages and incentives for its employees to improve employee performance.